Jemaah Islamiyah’s Collective Memories in Poso: Negotiated Bodies and Shifted Social Spaces - Amanah Nurish; Tsabita Afifah Khoirunnisa; Putri Suryani Samual; Tiara Amima Putri Dewi (Pascasarjana IAIN Pontianak, 2025)
This article traces the fragile and unfinished journeys of former Jemaah Islamiyah (JI) members as they attempt to re-enter the social fabric of Poso, Central Sulawesi. Through an anthropological lens, this study follows how their bodies bear the memory of conflict, how shifting social spaces reconfigure belonging, and how the disbandment of JI in 2024 unsettles older certainties while opening new dilemmas. Field observation from 2023 to 2025 was carried out through regular conversations, shared daily routines, and careful observation of how ex-militants negotiate presence and absence in communal life. The findings reveal that reintegration is not a straightforward passage from exclusion to acceptance, but a crossroads where ambiguities, fractures, and competing life orientations coexist. Rather than a linear process, it is lived as a series of negotiations—between stigma and recognition, faith and everyday survival, silence and speech. By situating these narratives within the anthropology of post-conflict regions, this article underscores the symbolic, interpretive, and relational dimensions of rebuilding social life, and calls attention to how the legacies of religious extremism are entangled with the embodied and spatial practices of return.